The Influence of Transformational Leadership and Work Motivation on Employee Performance at PT Sustraco Adikreasi During the 2021–2023 Period - Raihan Syahrul Ramadhan; Nur Asni Gani (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to determine the effect of transformational leadership and work motivation on employee performance at PT Sustraco Adikreasi for the 2021-2023 period. This type of research uses quantitative research, while the method used is the associative method. The population in this study was 64 employees of PT Sustraco Adikreasi. This research method uses non-probability sampling with 3 years of observation. The type of data used in this study is primary data. The data analysis method used in the study is an associative hypothesis with the help of IBM SPSS version 25.